In grandma's attic eaudiobook - Hanfield, Susan (christianaudio, 2016)
A young girl delights in her grandmother's stories of days gone by, sparked by keepsakes and simple questions, Grandma shares marvelous stories of mischief , discovery, and laughter, such as the time she accidentally lost the family buggy. Part of the bestselling Grandma's Attic series, these charming tales-updated with delightful new illustrations-will whisk you away to another time and place. And you'll find something worth far more than any treasure or keepsake...timeless lessons of life and faith!